2019
DOI: 10.1111/bju.14508
|View full text |Cite
|
Sign up to set email alerts
|

Extended periprostatic nerve distributions on the prostate surface confirmed using diffusion tensor imaging

Abstract: Different types of nerve fibers demonstrate distribution variations. When linked to possible functional aspects of the different nerve types, this morphologic evidence may be of importance to further protect function after radical prostatectomy. To our knowledge this is the first time that DTI confirmed reported histological findings in nerve sparing radical prostatectomies. DTI could be used as an important tool to correlate nerves-to-tumor for better pre-operative planning and incorporate imaging into the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Therefore, irregular hyperplasia of the prostate causes this angular position to change, which may affect the efficacy of anesthesia. Also, some studies found that NVB distribution is variable in some patients, and not all the peripheral nerves of the prostate are located at that angle (24). Hence, there is a need for a method that is sensitive enough to accurately position the NVB, to improve the anesthetic efficacy of PNB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, irregular hyperplasia of the prostate causes this angular position to change, which may affect the efficacy of anesthesia. Also, some studies found that NVB distribution is variable in some patients, and not all the peripheral nerves of the prostate are located at that angle (24). Hence, there is a need for a method that is sensitive enough to accurately position the NVB, to improve the anesthetic efficacy of PNB.…”
Section: Discussionmentioning
confidence: 99%
“…The neurogenic contractions induced by EFS reflect the tissue depolarization and consequent neurotransmitter release from the autonomic fibers. In the prostatic tissue from humans and rodents, noradrenaline is the main neurotransmitter released upon neuronal depolarization (Sievert et al, 2019;Pennefatheret al, 2000). This neurotransmitter elicits smooth muscle contraction through post-junctional α1-adrenoceptor stimulation, Gq protein activation and Ca 2+ -IP 3 signaling-based downstream (Michel, Vrydag, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate smooth muscle is highly innervated by excitatory and inhibitory autonomic neurons, which play a key role in the organ physiology (Sievert et al, 2019). The adrenergic nerves are the main pathway in several species and are responsible for the prostate smooth muscle contraction (Calmasini et al, 2015;…”
Section: Introductionmentioning
confidence: 99%
“…In addition, immunostaining of nerve fibers using RP specimens reported that 25% of all nerves were located in the anterolateral and anterior section of the prostate, suggesting that nerve damage is inevitable during RP, although it depends on the degree of NS. It is thought that nerve damage is inevitable during RP [27].…”
Section: Pathophysiology and Anatomy Of Erectile Functionmentioning
confidence: 99%